Maskulinitas Baru: Redistribusi Kerja Perawatan dalam Perspektif Feminisme - Boangmanalu, Abby; Aprilia, Iqraa Runi (Jurnal Perempuan, 2023)
Gender inequality in the workplace is rooted in patriarchal norms within families, institutions, and states. Gender roles exclude women from job opportunities, promotions, equal income, and more. Care work, associated with women, often forces them to choose between a career and family caregiving. However, a feminist perspective advocates for the redistribution of care work involving men. This research emphasizes the importance of changing men’s understanding and practices in care work to achieve gender equality in the workforce. Through in-depth interviews, the study critiques and synthesizes challenges in care work redistribution, shares successful practices, and recommends practical and conceptual suggestions to ensure men’s involvement in caregiving within the workplace context.